Reproductive efficiency in high and low body weight Nilagiri ewes subjected to short term flushing and PMSG treatments - KUMAR, R ANIL; IYUE, M; SRINIV ASAN, P (The Indian Journal of Animal Reproduction, 2023)
Economics of sheep breeding is largely dependent on reproductive efficiency which include conception rate, litter size and percent of weaned lamb. Besides selection for high reproductive efficiency, non-genetic measures like flushing and exogenous hormone treatment can be adopted to increase the reproductive efficiency. Short term flushing (group I), 250 IU of PMSG ( group II) and combination of I and II (group III) were used in 2 groups of ewes weighing above (A) and below (B) average to improve overall reproductive efficiency. The tupping percentage was 100 % in Group II and III. The percentage of tupping, lambing, twinning, number of lambs born, percentage of pre weaning mortality in different groups were 86.67,96.15,8,1.08,3.70 (group A I), 100,93.3,42,1.5,14.29 (group A II), 100,80,50,1.30,41.67 (group A III), 86.67,80.77,33,1.33,10.71 (group B I), 100,86.67,38,1.30,30.77 (group B II), 100,93.3,36,1.79,25 (group B III) as compared to 93.33,100,0,1,7.14 and 66.67,90,0,1,0 in 2 control groups. Based on litter size, lamb mortality and % lambs weaned it was observed that use of PMSG and flushing had increased reproductive efficiency. Higher dose rate of PMSG is needed in ewes weighing heavier at breeding and ewes which weigh less need not be subjected to superovulatory treatments but can be effectively flushed before breeding.